Contemporary learning techniques for healthcare professionals: A narrative review - Pandit, Anand S. (Frontiers in Education, 2022)
Background As medical knowledge continues to expand at an accelerated rate, healthcare professionals face a significant challenge in remaining up-to-date. Learning methods that can be utilised by staff in the clinical workplace are generally under-taught. The goal of this narrative review was to present evidence-based learning techniques that could aid postgraduate clinical education. Design Articles were sought for using PubMed, Ovid, PsychINFO, ERIC databases and other medical and non-medical databases. Using references from the initial search data, additional literature was identified. Articles were only included if relevant to the review objective. Results A total of 104 articles, chapters and books were used to compose this narrative review. An additional 135 articles and chapters were examined in full for context, including literature related to learning theory and workplace learning in other industries. The review is divided into two sections: (1) strategies that can help foster a learning mind-set; and (2) high yield practical tools that are effective in formal and informal learning domains. Conclusions Individual learning is a cornerstone of clinical performance, which influences the quality of care that one can deliver. Healthcare staff should be motivated to learn and to actively engage with the learning process. To that end, this review offers a comprehensive set of learning tools for individuals across a variety of settings.